Fine characterization technique of concealed channel and its application in the Jurassic Formation of western Sichuan Depression - LI Mengqiao, YE Tairan, DING Weinan, LIU Xingyan (Youqicang pingjia yu kaifa)
The sandstone reservoirs in the Jurassic formation of gas fields such as ZJ, XC, and SF in western Sichuan Depression are characterized by their tight nature and are primarily situated within delta plain-frontal distributary channels. These reservoirs often pose a unique challenge in terms of geophysical analysis due to the significant impedance contrast between the type ③ reservoir and the surrounding rock formations. Therefore, the precise characterization of concealed channel distribution is a crucial focus for expanding exploration and development efforts. In this study, the rock physics characteristics of reservoirs and forward modeling of AVO（Amplitude Versus Offset） gathers were conducted to determine the relationship between different reservoir types and AVO responses. Furthermore, a method known as the FN stacking method was developed. By optimizing the processing of gathers and selecting far/near offset stacking, the identification capability of concealed channels was significantly enhanced. This technology accurately reveals the distribution of hidden channels, precisely traces their shape and boundaries, and has successfully discovered new channels that have been confirmed through actual drilling, thus expanding new exploration and development fronts.